The faith of biology and the biology of faith order, meaning, and free will in modern medical science. - Pollack, Robert, 1940- (New York : Columbia University Press, 2013)
Are there parallels between the ""moment of insight"" in science and the emergence of the ""unknowable"" in religious faith? Where does scientific insight come from? Award-winning biologist Robert Pollack argues that an alliance between religious faith and science is not necessarily an argument in favor of irrationality: the two can inform each other's visions of the world.Pollack begins by reflecting on the large questions of meaning and purpose?and the difficulty of finding either in the orderly world described by the data of science. He considers the obligation to find meaning.
Cover; Half title; Title; Copyright; Series Page; Dedication; Contents; Preface to the 2013 Paperback Edition; Preface; Acknowledgments; Introduction; Chapter 1. Order Versus Meaning: Science and Religion; Chapter 2. The Meaning Is in the Order: DNA-Based Medicine; Chapter 3. Meaning Beyond Order: The Science of One Life at a Time; Postscript; Bibliography; Index
Description based upon print version of record.
Keywords: Free will and determinism; Genetics -- Moral and ethical aspects; Judaism and science; Meaning (Philosophy) -- Religious aspects; Natural selection; RELIGION / Religion & Science; Judaism and science; Meaning (Philosophy) -- Religious aspects; Natural selection; Free will and determinism; Genetics -- Moral and ethical aspects; Electronic books